Language Learning and Use in English-Medium Higher Education - Blaj-Ward, Lia (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book critically refines and adds depth to current understandings and practices in EAP (English for Academic Purposes) and EMI (English-Medium Instruction), using empirical research examining the experiences of English language learning and use of undergraduate and postgraduate international students in the UK. The author illuminates the language learning that takes place in and around English-medium higher education settings, both formally and informally, with a specific focus on courses with a creative or professional practice orientation. Drawing on theoretical insights from socio-cultural Second Language Acquisition, this volume capitalises on the synergies between applied linguistics and higher education research to paint a richer picture of the interactions facilitating student growth as confident and competent communicators in globalised academic and professional settings. Considering the broader implications of language development initiatives, this volume will be of interest to students and scholars of applied linguistics, English as a Second Language and second language acquisition. Lia Blaj-Ward is Senior Lecturer at Nottingham Trent University, where she coordinates in-sessional EAP provision for courses with an art, design or built environment focus. She is the author of Researching Contexts, Practices and Pedagogies in English for Academic Purposes (Palgrave Macmillan, 2014).
Keywords: Linguistics.; English language.; Discourse analysis.; Multilingualism.; Language and education.; elektronické knihy; electronic books